If the equation ∣ z − z 1 ∣ 2 + ∣ z − z 2 ∣ 2 = k represents the equation of a circle, where z 1 = 2 + 3 i and z 2 = 4 + 3 i are the extremities of a diameter, then the value of k is:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yes , that's it ! Good work , upvoted . : )
Let P ( z ) be a point on the circle with A ( z 1 ) and B ( z 2 ) as extremities of a diameter . Using the property that angle in a semicircle is 2 π ,
A P 2 + B P 2 = A B 2 ( Pythagoras’ theorem) ⟹ ∣ z − z 1 ∣ 2 + ∣ z − z 2 ∣ 2 = ∣ z 1 − z 2 ∣ 2 = ∣ 2 + 3 i − 4 − 3 i ∣ 2 = 4
∴ k = 4
Problem Loading...
Note Loading...
Set Loading...
This may look like a brainful at first, but it's actually pretty easy to solve. Remember that a diameter has endpoints (extremities) that are on the circle . This is the key, because it means that both endpoints ( z 1 and z 2 ) will satisfy the equation. Therefore, I plugged in z 1 into the equation to get: ∣ z 1 − z 1 ∣ 2 + ∣ z 1 − z 2 ∣ 2 = k Simplify some: ∣ 0 ∣ 2 + ∣ z 1 − z 2 ∣ 2 = k 0 2 + ∣ z 1 − z 2 ∣ 2 = k 0 + ∣ z 1 − z 2 ∣ 2 = k ∣ z 1 − z 2 ∣ 2 = k Now substitute the values of z 1 and z 2 in: ∣ 2 + 3 i − ( 4 + 3 i ) ∣ 2 = k Simplify some: ∣ 2 + 3 i − 4 − 3 i ) ∣ 2 = k ∣ − 2 ∣ 2 = k 2 2 = k 4 = k Now use the Symmetric Property of Equality: k = 4